The Phenylpropanoid Case – It Is Transport That Matters - Biała, Wanda; Jasiński, Michał (Frontiers in Plant Science, 2018)
Phenylpropanoids fulfill numerous physiological functions, essential for plant growth and development, as well as plant–environment interactions. Over the last few decades, many studies have shown that exquisite regulatory mechanisms at multiple levels control the phenylpropanoid metabolic pathway. Deciphering this pathway not only provides a greater, basic understanding of plant specialized metabolism, but also enhances our ability to rationally design plant metabolic pathways for future applications. Despite the identification of the participating enzymes of this complex, biosynthetic machinery, we still lack a complete picture of other genes, enzymes, and metabolites essential for regulation and compartmentation/distribution of phenylpropanoids. Compartmentation, as well as distribution, are critical for the fate/functioning of those molecules, and their effective biosynthesis. At the cellular level, we have narrowed down our understanding of these processes to organelles. Furthermore, various, overlapping, but not exclusive scenarios of phenylpropanoid distribution within the cell have also been described. The cross-membrane dynamics, but also intercellular communication of different branches from phenylpropanoid biosynthesis have become an exciting research frontier in plant science. The intra- and intercellular channeling of intermediates by various transport mechanisms and notably membrane transporters could be a meaningful tool that ensures, inter alia, efficient metabolite production.